The Impact of Servant Leadership and Work Discipline on Employee Performance at PT. X Call Center Section X - Ricky Nugraha; Muji Rahayu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The focus of this research is to investigate the effect of servant leadership and work discipline on the performance of PT X employees in the X call center section. This research is a descriptive quantitative research. The population is the employees of the call center section of PT X. The sampling technique utilizes saturated sampling technique, namely all members of the population are sampled, totaling 61. Data collection was carried out by distributing questionnaires scored according to the Likert scale. In order to examine how servant leadership and work discipline affect employee performance, researchers used a correlation approach, determination test, partial test, simultaneous test, and multiple linear regression. The results of hypothesis testing show that both together and partially, servant leadership and work discipline have a positive and significant influence on employee performance. The results can be interpreted that a high level of servant leadership and discipline can produce high performance.